Penerapan MDA Framework dalam Pengembangan Gim Tower Defense - Moh. Faiz Hidayatulloh; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Tower defense is a subgenre of strategy games that have been popular in the last two decades. In tower defense games, players must achieve their goals by defending territory and property by blocking attackers or stopping opponents from reaching an exit by laying defensive structures along the path of the opponent. One of the obstacles to tower defense games is an imbalance, for example a game that is too easy makes players bored quickly, while a game that is too difficult makes players frustrated. This can result in player disappointment resulting in negative feedback to the developer. To overcome these obstacles, a good development method is needed, one of the most widely used game design methods is the MDA framework. MDA stands for mechanics, dynamics, aesthetics. Each of the three represents the main elements in the game, namely the rules, game system, and player reactions. The purpose of modeling tower defense games into MDA is to make it easier for the development team to understand the elements of tower defense games from the perspective of developers and players according to the MDA function, so that the games created can be easily developed and get good feedback from players. From the test results through the playtesting method, it was found that players were satisfied with the game from the tower defense strategy game developed and gave positive feedback to the game and the developer.